EVALUASI PROGRAM PEMBELAJARAN BERBASIS HOTS (HIGHER ORDER THINKING SKILLS) DI MI AT-TAQWA GUPPI WOJOWALUR YOGYAKARTA TAHUN AJARAN 2018/2019 - Iskandar, Wahyu (Prodi PGMI STIT Al-Ittihadiyah Labuhanbatu Utara, 2020)
Abstract: Examining in more detail the discourse of the 2013 curriculum will ultimately pay attention to the learning process and items based on Higher Order Thinking Skills (HOTS) to students. Functionally HOTS is guaranteed to be very representative to sharpen higher-order thinking skills such as logical, reflective, critical, creative and metacognitive students. This research is very focused in exploring the evaluation of HOTS-based learning programs at MI At-Taqwa GUPPI Wojowalur Yogyakarta in the 2018/2019 academic year. Researchers chose MI At-Taqwa GUPPI Wojowalur Yogyakarta Special Region as the research location. Descriptive qualitative research is considered important as an alternative methodology in this paper. Data were analyzed, described and efforts were made to describe the data according to the principles of qualitative research. Retrieval of observation data, interviews and documentation. In this study, the speakers were the homeroom teacher and grade VI students at MI At-Taqwa GUPPI Wojowalur. The results of this study indicate that the evaluation of the HOTS learning program at MI At-Taqwa GUPPI Wojowalur Yogyakata in the 2018/2019 academic year the teacher carried out the learning by giving question items and discussing the grid before USBN related to the HOTS abilities of students from the books that had been prepared. . The books that contain USBN exam questions and their grids include Seconds Seconds of USP SD / MI Examinations Organized by the Education Unit for the 2019/2020 Academic Year published by PT Penerbit Intan Pariwara and Al Gendon Pediksi's Success Book for SD / MI School Exams 2019 / 2020 issue of Al-Gendon.